2010
DOI: 10.5352/jls.2010.20.4.496
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Grape Seed Proanthocyanidin Extract in Fibromyalgia Animal Model

Abstract: The acidic saline animal model of pain has been suggested to mimic fibromyalgia (FM). Oligomeric proanthocyanidin complexes (OPC) from grape seeds are known to act as an antioxidant. We studied the effects of OPC on the pain threshold in the acidic saline animal model of pain. The left gastrocnemius muscle was injected with 100 μl of saline at pH 4.0 under brief isoflurane anesthesia on days 0 and 5. Control rats (n=5) received identical injections of physiological saline (pH 7.2) on the same schedule. Rats (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Curcumin has been used for centuries in Indian and Chinese medicine due to its ability to impact a diverse range of molecular targets. Many studies using mice and rats have demonstrated that this bioactive compound has anti-inflammatory and antioxidant potential by suppressing numerous cell-signaling pathways, including nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), signal transducer and activator of transcription 3 (STAT3), nuclear factor-erythroid factor 2-related factor 2 (Nrf2), ROS, cyclooxygenase-2 (COX-2), superoxide leukocyte recruitment, and oxidative stress [ 48 ].…”
Section: Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin has been used for centuries in Indian and Chinese medicine due to its ability to impact a diverse range of molecular targets. Many studies using mice and rats have demonstrated that this bioactive compound has anti-inflammatory and antioxidant potential by suppressing numerous cell-signaling pathways, including nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), signal transducer and activator of transcription 3 (STAT3), nuclear factor-erythroid factor 2-related factor 2 (Nrf2), ROS, cyclooxygenase-2 (COX-2), superoxide leukocyte recruitment, and oxidative stress [ 48 ].…”
Section: Curcuminmentioning
confidence: 99%
“…In terms of FM-like symptoms using animals, Mun et al reported oligomeric proanthocyanidin complex (OPC) administration had anti-hyperalgesic effects in an acidic saline animal model that mimics fibromyalgia, due to OPC’s antioxidant and anti-inflammatory properties [ 48 ]. In the same animal study, authors found a decreased ASIC3 expression, an ion sensing channel present in central and peripheral nervous systems, in the M1 and M2 brains of hyperalgesic animals [ 48 ].…”
Section: Grape Seed Extractmentioning
confidence: 99%